Peranan Abdur Rahim Damrah dalam Melawan Penjajahan Jepang di Kabupaten Bengkulu Selatan (1943-1945) - Juliana Juliana; Bedriati Ibrahim; Bunari Bunari (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2022)
Abstract: The history of the Indonesian nation is a long historical journey. In general, the Indonesian people were colonized for three and a half centuries by European countries, such as the Portuguese, Spanish, British, Dutch, and occupied for three and a half years by the Japanese. Indonesia at that time was a country that had rich and abundant natural resources. The Japanese have entered Indonesia since March 1, 1942. The Japanese territory the Island of Sumatera was centered in Bukittinggi.The Japanese successed in taking control of South Bengkulu on February 24, 1942. During 1942 Japan lauched its colonial action in South Bengkulu by expanding its territory. This research uses historical research methods. The results of the research on the role of Abdur Rahim Damrah in the fight against Japanese Colonalism in South Bengkulu in 1943-1945 were initiated by Abdur Rahim Damrah attending Gyugun education in Pagaralam. Abdur Rahim Damrah becomes the leader Penjaga Keamanan Rakyat (PKR) in South Bengkulu, he led the battles against the Japanese army. Armed with Gyuguns previous military education, he fought against the Japanese occupation in South Bengkulu. Discussion and consolidation of the leaders and people of South Bengkulu was carried out, after the consolidation was completed they immediately moved to attack Japan. Because of the attack, Abdur Rahim Damrah was arrested and punished.